OPTIMALISASI PENATAAN ARSIP INAKTIF PADA RECORD CENTER DINAS PEMBERDAYAAN PEREMPUAN PERLINDUNGAN ANAK PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DP3AP2KB) PROVINSI JAWA TENGAH - Farisa Rahmawati; Yayuk Endang Irawati (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
Inactive archive management as part of archive maintenance is important to maintain authenticity, integrity, security and ensure the availability of information on files. As a file maker, the Central Java Provincial Office of Women's Empowerment, Child Protection, Population Control and Family Planning (DP3AP2KB) needs to organize files so that they are effective and efficient. Records Center is part of an inactive records management program. Inactive archive files stored in the record center for various lengths of time. Although the usefulness of information recorded in inactive archives has decreased, it still occasionally needs to be accessed as support for the implementation of its creation work. With this in mind, inactive archives are then processed and stored at the archive center. Inactive archives are then processed and stored at the archive center. The purpose of this research is to demonstrate to the wider community the role of archives centers. This research uses archival and qualitative methods.